Rare diseases in the genomic health care: Opportunities and challenges in India - Dipanjana Datta (Apollo Medicine)
In India , marriage in communities and families, makes the people more susceptible to accumulation of negative genetic traits , that can lead to a number of genetic disorders. Rare diseases are encountered in small fraction of the population with incidence of less than 1 in 2000. There are at least 7000 rare recognizable diseases with around 3000 more remain to be accounted for. Rare diseases are causally heterogeneous with 80% being of genetic origin. Detailed clinical and genetic investigations are crucial to diagnosis. In the current healthcare scenario, genetic diagnosis is not accessible in a resource limited set up . This article looks into genomic challenges of rare diseases in India, specifically the allele frequency in the normal population, essential for interpreting significance of variants. Research efforts in rare diseases of India are discussed for diagnosis and novel therapeutic explorations. Population databases, disease registry , and newer diagnostic techniques can help in understanding the rare diseases epidemiology in heterogeneous populations across India. This can help reduce cost and have targeted investigations, that will help in early diagnosis and early intervention.